Qualitative insights of patients and carers under the care of nurse navigators. Issue 1 (February 2019) - Hudson, Adrienne P.; Spooner, Amy J.; Booth, Natasha; Penny, Robyn A.; Gordon, Louisa G.; Downer, Tai-Rae; Yates, Patsy; Henderson, Robyn; Bradford, Natalie; Conway, Aaron; O'Donnell, Christopher; Geary, Alanna; et al.
Abstract: Background: Nurse navigator roles aim to assist patients and their carers with navigating the healthcare system and accessing services to enable them to take a more active role in their own health care. Aim: The aim of this study was to explore patients' and carers' experiences of receiving care from a nurse navigator. Methods: This was a qualitative study involving semi-structured interviews with 12 patients (adults and children) and 13 carers receiving care from a nurse navigator in Queensland, Australia. Thematic analysis was conducted. Findings: The nurse navigator was a central contact person for patients and carers within the complex healthcare system. They were described as approachable, available and knowledgeable about the medical condition and the healthcare system, enabling patients to take a more active role in their own healthcare. The navigators played a pivotal role in navigating the seemingly insurmountable obstacles of accessing advice, services, equipment and appointments in a seamless way. However, further work is required to ensure that patients and carers are connected with a nurse navigator earlier in their healthcare journey. Discussion: The nurse navigators' understanding of the complex healthcare system coupled with their global overview of patients and carers provided the participants with a sense of direction, options and more control over their own healthcare trajectory. Conclusions: The nurse navigator role has the ability to improve the care experience of patients and carers of varying ages and with varying medical conditions as explored in this study.